Still poorly adopted in male professional football: but teams that used the Nordic Hamstring Exercise in team training had fewer hamstring injuries - a retrospective survey of 17 teams of the UEFA Elite Club Injury Study during the 2020-2021 season - Ekstrand, J.; Bengtsson, H.; Walden, M.; Davison, M.; Hagglund, M. (BMJ Open Sport & Exercise Medicine, 2022)
Objectives: The primary objective was to study the adoption of the NHE programme in European football teams in the 2020/21 season and to compare it to the previous study. A second objective was to compare hamstring injury rates between teams that used the NHE programme in the team training and teams that used the NHE only for players with previous or current hamstring injuries.